The usefulness and effectiveness of argumentative writing self-assessment checklist in undergraduate writing classrooms - Vasu, Kayatri; Hossein, Vahid Nimehchisalem; Yong, Mei Fung; Md Rashid, Sabariah (Human Resource Management Academic Research Society, 2018)
Writing instruction in the ESL classroom has evolved dramatically over the last few decades. Now, the focus has shifted from the final product of writing to the process of writing. The writing process is divided into three main stages: prewriting, writing and rewriting (Murray, 1985). This change has encouraged educators to look for strategies that focus on the writing process systematically and involve the learners to be focused and active at every stage of writing. One of the strategies that has been gaining popularity is self-assessment. It refers to teaching methods such as self-assessment checklist that prompt student writers to carefully think about, assess and respond to their written work systematically (Nielson, 2014). This study investigates the perception of teachers and students on the usefulness of a self-assessment checklist to assist students in the argumentative writing. Self-assessment Checklist for Undergraduate Argumentative Writing designed by Nimehchisalem et al. (2014) is used in this study. Feedback was obtained from four university writing lecturers through the Delphi method. The checklist was then implemented in the undergraduate writing classroom for a period of five weeks and students’ perception on the usability of the checklist was recorded through interviews. Observations were made to understand the implementation process of the checklist. From the experts’ feedback, a few changes were made to the checklist by adding, deleting, rewording and re-arranging items to ensure the checklist is more user- friendly. The experts perceived the checklist to be an effective tool in that it would reduce their workload especially regarding the amount of time spent providing feedback to the students. Students reported the checklist motivated them to write, created awareness on their writing ability, enhanced their understanding of argumentative writing, made them independent writers, and assisted them in writing more systematically. The observation enlightened the researchers on the items that needed more assistance or explanation from teacher during the training session.